The Effect Of Group Investigation (GI) Learning Model Based On La-boratory Experiment Skills On Newton’s La Material In Grade X Of Senior High School Negeri 2 Percut Sei Tuan Academic Year 2024/2025: Jurnal Pendidikan - Pinondang Hutapea (Insan Akademika Publications, 2025)
Abstract: Generic (basic) thinking skills can be developed through studying physics. These skills are simpler in nature and can help students think at higher levels, as complex, critical, and creative thinking. The purposes of this research was to: To determine the differences in generic skills due to the effects of the GI type cooperative learning model and the DI model., To find out the difference between high generic laboratory skills and low generic skills. To find out wheter there is an interaction between the Group Investigation type and Direct Instruction type models on students generic skills to improve learning outcomes. The population in the study were all students of class X semester I of Senior High School Negeri 2 Percut Sei Tuan Academic Year 2024/2025 as many as 6 classes (228 people). This research is a quasi-experimental type, with a two-group pre-test and post-test design The research sampel consistet of 2 classes, namely class X-1 and class X-2 which were taken using cluster random sampling, class X-2 was taught with the GI model (experimental class) and class The results of testing using ANOVA two lanes can be concluded that there is an interaction between the GI model and laboratory skills on generic science abilities. The percentage increase in learning outcomes for the experimental class (74.7%) was greater than the percentage increase in learning outcomes for the control class (60.9%) with a difference in improvement between the experimental and control classes of (13.8%). From the calculation results, the percent increase in learning outcomes for the experimental class is higher than the learning outcomes for the control class. This shows that there is a significant difference in the percentage of Physics learning outcomes taught using the GI type learning model with the Physics learning outcomes taught using the DI model